PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 REMBOKEN - Manaida, Militia Christi; Sasinggala, Metilistina; Posumah, Dany Ch (LPPM Politeknik Saint Paul Sorong, 2024)
This study aims to apply the Team Assisted Individualization (TAI) cooperative learning model on the material of the human circulatory system to the learning outcomes of Biology students in class XI IPA 1 at SMA N 1 Remboken in the 2021/2022 academic year. This research is a type of class action research (PTK). The average value of teaching completeness in cycle I obtained from Xl IPA 1 class students with the Team Assisted Individualization teaching model was 41,66% and in cycle II it progressed with an average completeness value of 83,33%. In the results of the research that has been carried out, it is concluded that the implementation of Team Assisted Individualization (TAI) can improve student learning outcomes on the material taught as seen from the results of the evaluation of students in cycle II, an increase of 83,33% has met the standard of completeness from cycle I